Staat versus Querdenker: Eine sozial- und kommunikationspsychologische Betrachtung der Coronavirus-Pandemie - Ramona Golindano Acevedo; Julia Pitters (IUBH Internationale Hochschule, 2021)
– The coronavirus pandemic imposes major challenges for both the population and political actors. Measures to contain the pandemic must be communicated in such a way that they motivate to persevere. However there is now great resistance in parts of the population. From the perspective of social- and communication psychology, the present contribution considers the reasons for the formatting of two camps within the Federal Republic of Germany - in relation to the lateral thinker movement and the federal government. The focus is on the differences between the two groups' points of view, the resulting communication problems, and the group dynamics that lead to aggressive outbursts, especially in the Querdenker-movement. Finally, we discuss how these communication breakdowns can be resolved.
Keywords: 300; Coronavirus-Pandemie; Querdenker; Kommunikation; kognitive Verzerrungen; Gruppendynamik